Experimental investigation of RC slabs strengthened with NSM CFRP system subjected to elevated temperatures up to 80 ºC - Silva, Patrícia Moreira (2016)
The application of carbon fibre-reinforced polymers (CFRP) according to the near-surface mounted (NSM) technique has proved to be one of the most effective systems to strengthen existing reinforced concrete (RC) members in flexure. In spite of that, there are many open issues that deserve investigation such as the effects of exposure to elevated temperatures on the flexural behaviour of RC slabs strengthened with NSM-CFRP systems. The present work aims to experimentally evaluate the mechanical performance of RC slabs strengthened with NSM-CFRP systems under elevated temperatures by using steady-state and transient heating situations combined with applied loads. The temperatures studied were: 20, 40, 50, 70 and 80 °C for the steady-state tests, and 20 and 80 °C for the case of transient tests. Deflections, strains, temperatures and loads were registered in all phases of the tests, in order to thoroughly analyse the response of the system in terms of the load-deflection curves, evolution of the strains of concrete, CFRP and bond stresses between epoxy adhesive and CFRP. The experimental results have shown that the RC slabs strengthened with NSM CFRP systems presented a slight decrease in the ultimate strength and a change on failure mode at the temperature of 80 °C only.